2021
DOI: 10.1109/access.2021.3106170
|View full text |Cite
|
Sign up to set email alerts
|

Drunk Driving Detection Using Two-Stage Deep Neural Network

Abstract: Drunk driving accidents have been rapidly increasing in recent times. Although the statistics show a decreasing trend in recent years, reports of drunk driving accidents are often seen in the news. To assess vehicle operators for drunk driving, the police still use breath-alcohol testers as the primary method. However, a certified instrument to measure alcohol consumption is expensive, and the mouthpiece used in the instrument is a consumable. Moreover, the breath detection method used involves contact measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Sharma and Sood [ 69 ] employed an alcohol sensor and air pressure sensor for sobriety checks, and ML algorithms for drivers’ drowsiness detection via camera. Chang et al [ 70 ] explored drunk driving detection via facial images and breath-alcohol tester from 124 subjects (ages 18–70) using simplified VGG and Dense-Net: VGG classified the age range of the subject while Dense-Net identified the facial features of drunk driving for alcohol test identification, as shown in Figure 6 C. The model achieved an accuracy of 87.44% and the results showed that (1) the ears, chin, forehead, neck, cheek, and other facial parts of subjects’ images are good characteristic areas for alcohol tests, and (2) age affects the identification results in the alcohol test.…”
Section: Driver State Monitoringmentioning
confidence: 99%
“…Sharma and Sood [ 69 ] employed an alcohol sensor and air pressure sensor for sobriety checks, and ML algorithms for drivers’ drowsiness detection via camera. Chang et al [ 70 ] explored drunk driving detection via facial images and breath-alcohol tester from 124 subjects (ages 18–70) using simplified VGG and Dense-Net: VGG classified the age range of the subject while Dense-Net identified the facial features of drunk driving for alcohol test identification, as shown in Figure 6 C. The model achieved an accuracy of 87.44% and the results showed that (1) the ears, chin, forehead, neck, cheek, and other facial parts of subjects’ images are good characteristic areas for alcohol tests, and (2) age affects the identification results in the alcohol test.…”
Section: Driver State Monitoringmentioning
confidence: 99%
“…Although existing work on driver state monitoring addresses safety-critical states such as drowsiness or distraction, previous attempts at detecting drunk driving with vehicle signals have not achieved sufficiently good results or were not rigorously evaluated (e.g., [17,35,47,48,52,83,98,100]). • Significance: Our system offers a viable approach based on existing technologies, allowing for a rapid implementation to prevent potential negative consequences of drunk driving after decades of stagnating high alcohol-related road crashes without any significant advancement by regulators and industry [67,90].…”
Section: Contributionsmentioning
confidence: 99%
“…Recently in [25], a two-stage deep learning approach is proposed to detect drunk driving using a Convolutional Neural Network (CNN). At first, the simplified VGG (Visual Geometry Group) network, a standard CNN, is applied to estimate the driver's age, and then the simplified Dense-Net for identifying the facial features of drunk driving for alcohol test discrimination.…”
Section: Related Workmentioning
confidence: 99%